Pengembangan Religiositas Anak melalui Pendidikan Agama Islam dalam Keluarga - Holik, Entis Abdul (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2016)
This research article found three conclusions as follows: First, there are several strategies used in the development of children through the religiosity of Islamic Education in the family in this village, namely: education strategies, ethical strategy, economic strategy, cultural strategy, and communication strategies. Strategy development religiosity education means children who rely on the activity of formal education, informal and non-formal. Ethical strategy is a strategy that was developed based on the values of ethics developed in rural communities. Economic strategy aimed at improving the welfare of family life and strengthen the economy. Cultural strategy is to introduce children to the cultural values that do not conflict with the teachings of Islam. The communication strategy is to develop good communication between parents and children in an effort to improve religious power in the face of rapidly changing times. Second, the development model of religiosity children through Islamic Education in families in this village is done by strengthening the education of children in the family through advice, example, guidance, and habituation values of faith and piety, such as establishing prayer, reading the Qur'an, charity, diligent prayer, doing good for others, honesty, and discipline. Third, the development of child religiosity through religious education in the family work (1) pressing and juvenile delinquency, (2) an increase in religious activities in mosques and mosque of the children, (3) an increase in the security environment of the village, (4) children free from the influence of alcohol and abuse of drugs.